Dermatan sulfate/chitosan polyelectrolyte complex with potential application in the treatment and diagnosis of vascular disease - Rasente, Rita Yanina (2016)
Cardiovascular disease is the largest single cause of morbid-mortality in the world. However, there is still no pharmaceutical treatment that directly targets the blood vessel wall instead of just controlling the risk factors. Here, we produced polyelectrolyte complexes (PECs) by a simple and reproducible polyelectrolyte complexation method between low molecular mass dermatan sulfate (polyanionic polysaccharide) and chitosan (polycationic polysaccharide), and evaluated the cellular uptake by vascular endothelial cells. The composition and the composition homogeneity of PECs were confirmed by 13C-CP-MAS spectroscopy and by polyacrylamide gel electrophoresis, respectively. The hydrodynamic radius, determined by dynamic light scattering, was 729 ± 11 nm. PECs were not cytotoxic for a murine heart endothelium-derived cell line. Fluorescent confocal microscopy showed the specific uptake of fluorescently-labeled PECs by endothelial cells when they were cultured alone or in the presence of macrophages. Overall, these findings confirmed the potential of these PECs for targeting different agents to the vessel wall in the prevention, diagnosis, and therapy of vascular disease.